Association of third molar eruption and frictional keratosis - a retrospective study - SUBRAMANIAN, VAISHNAVI SIVAKALI; G. MARAGATHAVALLI; KUMAR S, ARAVIND (The journal of contemporary issues in business and government, 2020)
Frictional keratosis represents increased keratin production in response to chronic mechanical irritation. The retromolar pad and edentulous alveolar ridge are the most common sites of involvement due to trauma from food being crushed against the mucosa during mastication. A fractured tooth or rough restoration may lead to the development of frictional keratosis on the adjacent lateral tongue or buccal mucosa.These lesions do not undergo malignant change and should resolve after the source of irritation is eliminated. The aim of the study was to investigate the association of a third molar eruption with frictional keratosis among the patients of Saveetha dental college. A total of 200 patients with keratosis were taken into the study from Saveetha Dental College, Chennai. The data was collected from case sheets of patients who reported for various dental treatments between the period of June 2019 to March 2020 which consists of patients’ demographic data, personal history, medical history, intra and extraoral findings and photographs which are taken with patients’ concern. Chi square test was done using SPSS..The results showed 20-30 year old patients were seen maximum with all the reported clinical findings.This proportion decreases with increase in age groups.Maxillary third molars had maximum number of buccoverted teeth (18 - buccoverted 21% and sharp cusp 3%) (28- buccoverted 9.5% and sharp cusp 6.5%) and mandibular third molars were reported with maximum number of sharp cuspal tips (38-35% sharp cusp and 5% buccoverted)(48- 9% sharp cusp and 1.5% buccoverted).Within the limitations of the study, the results show that buccoverted third molars are the most common reason that causes frictional keratosis followed by sharp cuspal tips and cheek biting habits. However tobacco pouch keratosis is also seen among the patients.